Integrated visual culture in Neo-Chinese branding: A semiotic analysis of CHAGEE’s packaging and digital campaigns - Erlyana, Yana; Hidajat, Henny; Sutanti, Keisya Annabella (Jurnal Desain, 2026)
The "Guochao" (Neo-Chinese) aesthetic trend has significantly transformed contemporary visual communication by redefining how traditional culture is represented in urban markets. This study explores CHAGEE’s visual culture to understand the deconstruction and modernization of historical Chinese elements through design. Utilizing a qualitative case study integrated with systematic digital archiving, the research applies Roland Barthes’ semiotic framework to analyze packaging designs (beverage cups) and digital social media campaigns. The analysis reveals that CHAGEE utilizes toile de Jouy motifs and constellation symbols on physical packaging to establish historical legitimacy, while digital media transcodes these elements into urban lifestyle narratives and emotional storytelling. These findings indicate that the synergy between physical and digital domains aims to construct modern myths of "authenticity through origin" and "urban escapism." This study concludes that integrating archaic physical design with dynamic digital narratives allows cultural heritage to be successfully translated into contemporary lifestyle branding that resonates with modern audiences.